Desempenho de juvenis de Pseudoplatystoma fasciatum alimentados com níveis crescentes de farelo de glúten de milho - Bicudo, Álvaro José de Almeida; Borghesi, Ricardo; Dairiki, Jony Koji; Sado, Ricardo Yuji; Cyrino, José Eurico Possebon (Pesquisa Agropecuaria Brasileira, 2012)
<span style="line-height: 115%; font-family: "TimesNewRomanPSMT","serif"; font-size: 10pt; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-bidi-font-family: TimesNewRomanPSMT; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">The objective of this work was to evaluate corn gluten meal (CGM) as a substitute for fish meal in diets for striped catfish (<span style="line-height: 115%; font-family: "TimesNewRomanPS-ItalicMT","serif"; font-size: 10pt; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-bidi-font-family: TimesNewRomanPS-ItalicMT; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">Pseudoplatystoma fasciatum<span style="line-height: 115%; font-family: "TimesNewRomanPSMT","serif"; font-size: 10pt; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-bidi-font-family: TimesNewRomanPSMT; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">) juveniles. Eight isonitrogenous (46% crude protein) and isoenergetic (3,450 kcal kg-1<span style="line-height: 115%; font-family: "TimesNewRomanPSMT","serif"; font-size: 6pt; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-bidi-font-family: TimesNewRomanPSMT; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US"> <span style="line-height: 115%; font-family: "TimesNewRomanPSMT","serif"; font-size: 10pt; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-bidi-font-family: TimesNewRomanPSMT; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">digestible energy) diets, with increasing levels of CGM – 0, 6, 12, 18, 24, 30, 36, and 42% –, were fed to juvenile striped catfish (113.56±5.10 g) for seven weeks. Maximum values for weight gain, specific growth rate, protein efficiency ratio and feed conversion ratio, evaluated by polynomial quadratic regression, were observed with 10.4, 11.4, 15.4 and 15% of CGM inclusion, respectively. Feed intake decreased significantly from 0.8% CGM. Mesenteric fat index and body gross energy decreased linearly with increasing levels of CGM; minimum body protein contents were observed with 34.1% CGM. Yellow pigmentation of fillets significantly increased until 26.5% CGM, and decreased from this point forth. Both plasma glucose and protein concentrations decreased with increased CGM levels. The inclusion of 10–15% CGM promotes optimum of striped catfish juveniles depending on the parameter evaluated. Yellow coloration in fillets produced by CGM diets can have marketing implications.